ANALYSIS OF EMPLOYEE CAREER MANAGEMENT IN THE BULUNGAN REGENCY GOVERNMENT FOLLOWING THE RECLASSIFICATION OF STRUCTURAL POSITIONS TO FUNCTIONAL POSITIONS - Muammar Gilang Azhar; Muliyadi Hamid; Ilham Safar (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2026)
This research is motivated by the position equalization policy, which drastically disrupts the career patterns of local government apparatus. The purpose of this study is to analyze the certainty of rank and the clarity of promotion paths for equalized functional officials, as well as its implications for the workflow rhythm and organizational mobility. The method used is descriptive qualitative research. Data collection was conducted through in-depth interviews with affected functional officials and administrator officials, supported by direct observation and analysis of staffing regulation documents within the Bulungan Regency Government. The results show that the integration of performance appraisal based on SKP conversion provides administrative convenience in regular employee promotion. However, this policy triggers a career shock due to the loss of clarity in horizontal promotion caused by the rigidity of national regulations and the limited quota of formations for the Intermediate Expert level in the region. From the organizational aspect, adaptation is carried out through the formation of Working Groups (Pokja) to replace the role of Echelon IV. This teamwork mechanism successfully cuts bureaucratic red tape, yet the loss of lower-level filtering roles instead multiplies the managerial workload of middle management (Echelon III). Furthermore, this mass transfer triggers severe task adjustment challenges, role ambiguity, and a slow learning curve for employees within the digital ecosystem. This phenomenon indicates a culture shock due to the deeply rooted traditional structural hierarchy birocracy at the regency level, which hinders the optimization of a flexible organizational model.